Al-Rabat and Khanat in the City of Jerjan and its Scientific and Social Role through the Book " The History of Jerjan " by Hamzah bin Yusuf Al-Sahmi - رجب, وائل (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research dealt with the Study of public service institutions in the City of Jerjan, represented by Al-Rabat and Khanat established in them and to identify the scientific and social role of these institutions through the Book "The History of Jerjan" by Hamzah bin Yusuf Al-Sahmi. The research included an Introduce and several axes, The First axis discussed the life of Al-Sahmi in two parts, The First dealt with his name, lineage, death and his most prominent writings. The second section dealt with the Book "The History of Jerjan" and Al-Sahmi's approach in writing this book. As for the Second and Third axes, each of them dealt with the most prominent Al-Rabat and Khanat that were established in the City of Jerjan during the research period _ between the first and fifth Centuries H ̸ seventh and eleventh Centuries A.C _ and its Impact on the scientific and social life in the city of Jerjan. The Fourth axis dealt with the extent of the impact of the phenomenon of endowments, which was widespread in the Arabic Islamic Society, in supporting these institutions and ensuring their continuity in the services they provide, whether on the scientific or social level. The research also included a mention of the most prominent conclusions that came out with it.